2018
DOI: 10.1590/2236-8906-47/2018
|View full text |Cite
|
Sign up to set email alerts
|

Flora Polínica da Reserva do Parque Estadual das Fontes do Ipiranga (São Paulo, SP, Brasil). Família: 88 - Myrtaceae

Abstract: RESUMO No presente trabalho foram estudados os grãos de pólen de 55 espécies pertencentes a 15 gêneros da família Myrtaceae ocorrentes na “Reserva do Parque Estadual da Fontes do Ipiranga”. Os seguintes táxons são incluídos: Blepharocalyx salicifolius (Kunth) O. Berg, Calyptranthes concinna DC., C. grandifolia O. Berg, Campomanesia eugenioides (Cambess.) D. Legrand ex Landrum, C. guaviroba (DC.) Kiaerk., C. guazumifolia (Cambess.) O. Berg, C. phaea (O. Berg) Landrum, C. pubescens (DC) O. Berg, Eugenia beaurepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Silveira-Júnior et al (2012) observed that pollen grains of Richardia grandiflora were large-sized and suboblate, differing from our present observations. For Myrtaceae, our observations for Psidium guajava agree with the descriptions provided by Corrêa et al (2018) in their small size and oblate shape.…”
Section: Pollen Morphology Of Bee Plant Speciessupporting
confidence: 90%
“…Silveira-Júnior et al (2012) observed that pollen grains of Richardia grandiflora were large-sized and suboblate, differing from our present observations. For Myrtaceae, our observations for Psidium guajava agree with the descriptions provided by Corrêa et al (2018) in their small size and oblate shape.…”
Section: Pollen Morphology Of Bee Plant Speciessupporting
confidence: 90%
“…Our main goal is to investigate whether pollen attributes could be useful for species distinction within the genus. Based on previous pollinic studies within Myrtaceae (Barth and Barbosa 1972;Thornhill et al 2012aThornhill et al , 2012bThornhill et al , 2012cThornhill et al , 2012dTuler et al 2017;Corrêa et al 2018), we expect exine ornamentation, size and shape to be the most efficient pollen characters for distinguishing species or groups of species within Campomanesia.…”
Section: Introductionmentioning
confidence: 99%
“…Christensen 1986; Carrijo et al 2013; Silva-Fourny et al 2018; Oliveira et al 2019; Ragho 2020; Araújo et al 2021; Souza-Souza et al 2022) and has proven informative for delimiting species of Psidium L. (Tuler et al 2017), another genus of Pimentinae within Myrtaceae. However, few species of Campomanesia have had their pollen grain morphology described in the literature (Barth and Barbosa 1972; Thornhill et al 2012d; Corrêa et al 2018). Therefore, the role of pollen morphology in the taxonomy of Campomanesia remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations